Pertumbuhan Dan Kelulushidupan Ikan Lele Dumbo (Clarias gariepinus) Dengan Padat Tebar Berbeda Menggunakan Probiotik Boster Aquaenzyms Pada Pakan - Nurul Hayani Telaumbanua; Rusliadi Rusliadi; Niken Ayu Pamukas (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was conducted on November 7thto December 11th2017 in the laboratory of Aquaculture Technology, Marine and Fisheries Faculty, University of Riau, Pekanbaru. The main purpose of this study was to determine the best stocking density to increase the growth and survival rate of catfishby using aquaenzymsboster probiotics on feed. The method was an experimental method of completely randomized design (CRD) with one factor, four treatments and three replications. The treatments in this study were P1 (35 fish/72 liters), P2 (50 fish/72 liters), P3 (65 fish/72 liters), and P4 (80 fish/72 liters). The respecti vely rearing tanks were 12 unitsof aquarium by 60 cm x 40 cm x 40 cm and filled of 72 liters of water. Feed was given three times a day with 35% of protein dose. The result of the observation showed that the stocking density 50 fish/72 literswas the best stocking density in this study which providedthe absolute growth weights was 16.16 g, specific growth rate was 6.09%, absolute growth length was 8.92 cm, and survival rate was 89.33%. The water quality parameters were in thetolerance range of catfish where the temperature was 26-28 0C, pH was 5-6, DO (Dissolved Oxygen) was 4.0-5.0 mg/L and ammonia was 0.022-0.085 mg/L. Keyword: Probiotics, Stocking density, Clarias gariepinus, Growth